Properties of heteropoly compounds carried on θ-Al2O3 in the capturing of NOx using infra red spectroscopy (in situ) - V. A. Matyshak; N. V. Konokhov; V. F. Tret’yakov; M. D. Shibanova; J. P. Tyulenin; O. N. Sil’chenkova; V. N. Korchak (Тонкие химические технологии)
It was shown that carrying a small (up to 1%) amount of a heteropoly compound increases the adsorption of NOx as compared to the original carrier. The increase in adsorption is due to the oxidation of NO to NO2 on the carried heteropoly compound. The main adsorption factors are nitrite and nitrate complexes. Their place of localization is the carrier. As temperature increases, the complexes change to nitrates. The presence of ions of varying valencies in the composition of the Kegin anion reduces the strength of the bond of the nitrate complexes with the surface. The ions that are not in the Kegin anion increase the bond strength. The change in the strength of the bond of nitrates with the surface of the carrier is owned to the carrier modification, which results from disintegration of a part of the carried heteropoly compound.